Circularly polarised backward, broadside, and forward beam scanning cross‐slot loaded periodic planar leaky‐wave antenna. Issue 2 (5th January 2021) - Barzegari, Saeed; Forooraghi, Keyvan; Arand, Bijan A.
Abstract: In the present study, a novel periodic planar leaky‐wave antenna (PLWA) was designed, simulated, and fabricated based on the substrate integrated waveguide (SIW) technology. The antenna can scan the main beam from around −60° to +20° continuously with complete suppression of open stopband (OSB) by the sweeping frequency from 9.2 to 14.1 GHz. The proposed structure was designed to have circular polarisation (CP) in the entire operating frequency range, where the broadside or centre frequency is 12.25 GHz. Antenna gain in the broadside frequency is around 13 dBi. The radiation efficiency of the structure is improved and equalised through broadside, which is around 80% in the frequency band of operation. Also, series and shunt analysis was applied to the proposed periodic PLWA in the fundamental TE10 mode. In the next step, the asymmetric was applied longitudinally and transversely to the proposed structure to achieve OSB elimination combined with circular polarised radiation simultaneously. The equivalent circuit of the proposed structure was extracted and, finally, the antenna was fabricated. Based on the results, excellent agreement was observed between the measured, modelled, and simulated results.